Hidradenitis suppurativa in Down's syndrome: A case report - Nadeem Toodayan (Our Dermatology Online, 2015)
Of the many dermatological conditions thought to be linked with Down's syndrome, hidradenitis suppurativa presents a peculiar manifestation. This brief case report summarises the clinical features and possible genetic basis for this fascinating association.